Composition based on 2-oxoglutaric acid and preparation method

By wrapping 2-oxoglutaric acid with the synergistic effect of the vitamin composition, the problem of easy oxidation and degradation of 2-oxoglutaric acid in application is solved, and the stability of the drug is improved and the sustained release performance is enhanced, which significantly improves the efficiency of collagen production and tissue repair ability.

CN119564838AActive Publication Date: 2025-03-07HANGZHOU NUPTEC RISING BIOPRODUCTS INC LTD +1

Patent Information

Application Number
CN202510131066.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-07
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

2-oxoglutaric acid is prone to oxidation and degradation in practical applications, difficult to control release, and uneven distribution in the body, which limits its role and effect in collagen production.

Method used

Through the technical design of copolymer acid-encapsulated 2-oxoglutaric acid, combined with the synergistic effect of vitamin composition, the protection, stability improvement, controlled release and functional efficiency of functional components are achieved.

Benefits of technology

It significantly improves the antioxidant stability, sustained release performance and biocompatibility of the drug, achieves continuous and stable drug release, and improves the efficiency of collagen production and tissue repair ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564838A_ABST
    Figure CN119564838A_ABST
Patent Text Reader

Abstract

The invention relates to a composition based on 2-oxoglutaric acid and a preparation method of the composition. The composition comprises copolymer acid coated 2-oxoglutaric acid, nicotinamide, gamma-aminobutyric acid and the like. The copolymer acid is prepared through a double emulsification-solvent evaporation method, the used copolymer acid is polylactic acid-glycolic acid copolymer acid with the molecular weight of 15-20 kDa, and the average particle size of 2-oxoglutaric acid wrapped by the copolymer acid is 100-500 nm. The preparation method comprises the steps of solution preparation, emulsification, ultrasonic treatment, stirring, centrifugation and the like, and ensures the average particle size uniformity and the encapsulation efficiency of the nanoparticles. The composition promotes generation of collagen, improves physiological adaptability through an osmotic pressure regulator and a pH buffer solution, realizes stable encapsulation and slow release performance of 2-oxoglutaric acid, improves oxidation resistance and biocompatibility, and is widely applied to the fields of tissue repair and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical preparations, and in particular to a composition based on 2-oxoglutaric acid and a preparation method thereof. Background Art

[0002] In the field of modern medicine and bioengineering, the demand for chronic disease prevention, treatment, tissue repair and anti-aging is increasing. 2-Oxoglutaric acid has a significant effect on promoting collagen production in fibroblasts and skin epithelial cells, showing a wide range of application potential. However, the main challenges it faces in practical applications are easy oxidative degradation, high difficulty in release control and uneven distribution in the body, which significantly limit its effect in collagen production. Therefore, the development of delivery materials that can stably encapsulate and slowly release 2-oxoglutaric acid has become key. The ideal delivery system needs to have the following properties: First, the carrier material must have efficient encapsulation and protection properties to prevent 2-oxoglutaric acid from losing its activity due to oxidative degradation during processing and physiological environments, thereby ensuring its support for collagen production; second, the average particle size of the nanoparticles should be controlled within the nanoscale range to ensure targeted delivery and uniform distribution of the drug in the cell microenvironment, thereby improving the efficiency of promoting collagen production; third, the material must have excellent biocompatibility and environmental stability to avoid immune rejection and ensure its safety and activity in fibroblasts and skin epithelial cells; fourth, the material system should be able to accurately control the release rate of the drug, achieve a sustained release effect, and continuously promote collagen production over a long period of time. Breaking through the above properties will significantly improve the application effect of 2-oxoglutaric acid in collagen production, while enhancing patient compliance and promoting its widespread application in the fields of chronic disease treatment, tissue repair, beauty and skin care, and anti-aging.

[0003] In the prior art, although some progress has been made in the research on 2-oxoglutaric acid, there are still significant limitations in the application of promoting collagen production. For example, although the scheme with publication number CN103476274A proposes a combination of adding α-ketoglutaric acid, it does not adopt coating and antioxidant protection, resulting in unstable drug release rate and activity susceptible to oxidative degradation, and cannot continuously promote the production of collagen. In addition, the scheme lacks comprehensive regulation of material biocompatibility and osmotic pressure, and it is difficult to adapt to complex physiological environments, thereby limiting its practical application in the field of tissue repair and beauty. Further analysis found that these problems mainly come from the following reasons: First, no coating or loading treatment is adopted, resulting in the difficulty of accurately controlling the drug release rate and being unable to continuously support collagen production; second, no antioxidant protection system is introduced, so that 2-oxoglutaric acid loses its activity due to oxidative degradation during processing, storage and use; third, the material system lacks the optimization design of biocompatibility and osmotic pressure, resulting in its low adaptability in the cell environment. Therefore, it is urgent to develop an efficient delivery system to achieve the comprehensive performance of sustained and stable drug release, effective antioxidant protection, and promotion of collagen production. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide a composition based on 2-oxoglutaric acid and a preparation method thereof, so as to solve the problem that the current 2-oxoglutaric acid is insufficient.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A composition based on 2-oxoglutaric acid comprises the following raw materials in parts by weight: 10-20 parts of copolymer acid-encapsulated 2-oxoglutaric acid, 0.1-1.5 parts of nicotinamide, 0.2-1.0 parts of gamma-aminobutyric acid, 0.1-0.5 parts of superoxide dismutase, 2-6 parts of polyethylene glycol 400, 2.5-4.5 parts of pH buffer, 3.5-8.0 parts of bioremediation promoter, 0.5-4.5 parts of osmotic pressure regulator, 2.0-6.0 parts of beta-cyclodextrin, 50-70 parts of deionized water, 0.02-0.1 parts of pyrroloquinoline quinone disodium salt, 0.2-0.8 parts of catechin, 0.5-2.0 parts of L-carnitine, 0.5-2.5 parts of trisodium fructose-1,6-diphosphate, and 0.002-0.02 parts of vitamin B12; The copolymer acid-encapsulated 2-oxoglutaric acid is prepared by double emulsification-solvent evaporation method to prepare the polylactic acid-glycolic acid copolymer acid-encapsulated 2-oxoglutaric acid and vitamin composition; The polylactic acid-glycolic acid copolymer is obtained by polymerization of glycolic acid and lactic acid.

[0006] Further, the preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid is as follows: by weight, first, 0.5-1.5 parts of Tween 80 are dissolved in 20-40 parts of 2wt% citric acid aqueous solution, then 1.25-4.5 parts of the vitamin composition are added thereto, and then 45-65 parts of 2.0wt% polyvinyl alcohol aqueous solution are added, and after mixing evenly, a solution A is obtained, and then another 2.5-4.5 parts of 2-oxoglutaric acid are evenly dissolved in 60-85 parts of glycerol to obtain a solution B; then 10-20 parts of polylactic acid-glycolic acid copolymer acid are evenly dissolved in 100-200 parts of ethyl acetate to obtain an organic solution; after mixing evenly the solution A and the solution B in a mass ratio of 1:3, the solution A and the solution B are added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added to a vortex instrument container to emulsify the primary emulsion, the vortex time is 30-60s, and the vortex instrument speed is 2000-3000. rpm, then use an ultrasonic processor for ultrasonic treatment, the ultrasonic conditions are 10 seconds on / off cycle each time, the ultrasonic amplitude is 60~70%, the frequency is 20~24 kHz, and the number of ultrasonic treatment cycles is set to 3~5 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution are added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment are continued to form a double emulsion. The vortexing time is 5~10min, and the number of ultrasonic treatment cycles is 2~4 times. The treated double emulsion is added to a magnetic stirrer, and the stirring rate is set to 500~1000 rpm, the stirring temperature is 30~40℃, and the stirring time is 240~320min. After the stirring is completed, solid nanoparticles are obtained; then 10~18 parts of solid nanoparticles and 100 parts of deionized water are mixed evenly and centrifuged at 10000~15000rpm for 180~360s, and then the upper suspension after centrifugation is taken and dried under vacuum at room temperature. The vacuum conditions are 40~100 Pa, the drying time is 6 to 12 hours, and after complete drying, the copolymer acid encapsulating 2-oxoglutaric acid is obtained.

[0007] Furthermore, the mass ratio of the vitamin composition to 2-oxoglutaric acid is (0.5-1.0):1; Furthermore, the vitamin composition is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of (2.0-4.5):1:1.

[0008] Further, the preparation method of the polylactic acid-glycolic acid copolymer acid is as follows: by weight, 3.0-6.0 parts of glycolic acid, 12.9-25.8 parts of lactic acid and 3.0-5.5 parts of deionized water are stirred at 100-120° C. for 90-140 minutes, then cooled to 60-70° C., 0.10-0.25 parts of zinc lactate are added, stirred evenly, and then heated to 160-170° C., stirred and reacted under vacuum for 14-18 hours, and a Dean-Stark device is used during the reaction. The by-products are continuously removed, and after the reaction is completed, the temperature is reduced to 80-90°C, and then dried under vacuum conditions for 12-20 hours to obtain a crude copolymer product, and then the crude copolymer product is dissolved in 60-80 parts of ethanol to form a mixed solution, and then the mixed solution is added dropwise to a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:3. After the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove the residual solvent and retain the precipitate, and then the obtained precipitate is dried under vacuum conditions at 60-70°C for 18-24 hours, and then freeze-dried at -20°C for 36-48 hours to finally obtain a polylactic acid-glycolic acid copolymer.

[0009] The purpose of this scheme is to achieve the protection, stability improvement, controlled release and functional enhancement of functional ingredients through the technical design of copolymer acid encapsulating 2-oxoglutaric acid, combined with the synergistic effect of vitamin composition. Specifically, the use of copolymer acid can effectively encapsulate 2-oxoglutaric acid, forming a protective barrier to prevent its degradation in the external environment (such as light, heat, oxidation, etc.), and improve its stability; at the same time, the sustained-release characteristics of copolymer acid can achieve the precise release of 2-oxoglutaric acid in specific application scenarios, prolong its action time, improve bioavailability, and reduce the dosage and frequency of use. In addition, by introducing vitamin composition (vitamin D, vitamin B1 and vitamin B2), using its multifunctional characteristics (such as the immunomodulation and calcium-phosphorus metabolism of vitamin D, the metabolic support function of vitamin B1, and the antioxidant effect of vitamin B2), it forms a synergistic effect with 2-oxoglutaric acid to further enhance the biological functionality of the product. The mass ratio of the vitamin composition to 2-oxoglutaric acid is designed to be (0.5~1.0):1, and the ratio of each component in the vitamin composition (vitamin D: vitamin B1: vitamin B2) is (2.0~4.5):1:1, which ensures the scientific combination and functional balance of the two, and avoids functional weakening or potential adverse effects caused by imbalance of proportion. This scheme forms uniformly distributed and stable nanoparticles through the effects of emulsifiers and stabilizers such as Tween 80 and polyvinyl alcohol, combined with processes such as vortex treatment, ultrasonic treatment and vacuum drying. At the same time, key process parameters such as emulsification conditions, ultrasonic intensity and stirring rate are refined and optimized to ensure the stability and repeatability of the preparation process, thereby obtaining high-purity and stable solid nanoparticles. Through this design, this scheme can be widely used in the fields of drug delivery, functional foods, health products and biomaterials, providing efficient solutions for metabolic regulation, anti-oxidation and nutritional supplementation, while improving the functionality and market value of the product.

[0010] Furthermore, the molecular weight of the polylactic acid-glycolic acid copolymer is 15-20 kDa.

[0011] Furthermore, the average diameter of the copolymer acid encapsulated 2-oxoglutaric acid is 100-500 nm.

[0012] Furthermore, the mass ratio of glycolic acid to lactic acid is 1:4.3.

[0013] Furthermore, the biorepair promoter is hyaluronic acid or chitosan; Further, the osmotic pressure regulator is mannitol or sodium chloride; Further, the pH buffer is a phosphate buffer or a citrate buffer or a mixture of the two; Furthermore, the pH value of the composition based on 2-oxoglutaric acid is 6.8-7.2, and the osmotic pressure is 280-320 mOsm / L.

[0014] The present invention adopts the design of copolymer acid encapsulating 2-oxoglutaric acid, which is mainly used to enhance the stability, sustained-release performance and biocompatibility of 2-oxoglutaric acid. The molecular weight of polylactic acid-glycolic acid copolymer acid is 15-20 kDa, and the mass ratio of glycolic acid to lactic acid is 1:4.3, so that it has a suitable degradation rate and mechanical properties, and gradually degrades in the body to achieve precise sustained release. The average diameter of the nanoparticles formed by encapsulation is 100-500 nm, and the average particle size control optimizes the dispersibility, stability and in vivo absorption efficiency of the drug. The pH value is adjusted to 6.8-7.2 and the osmotic pressure is adjusted to 280-320 mOsm / L to further enhance the adaptability of the composition in a physiological environment and the protection of drug activity. As biorepair promoters, hyaluronic acid or chitosan improves the biological functionality of the composition by promoting tissue repair and providing antibacterial protection; mannitol or sodium chloride as osmotic pressure regulators ensures stability in the physiological environment and avoids the adverse effects of osmotic pressure fluctuations on drug release; pyrroloquinoline quinone disodium salt, as an active ingredient with antioxidant and cell protection functions, can effectively reduce the damage of oxidative stress to cells; catechins further enhance free radical scavenging ability through their strong antioxidant properties, and also have the effect of protecting cardiovascular health; L-carnitine is mainly involved in fat metabolism, promotes energy generation and improves cell activity; trisodium fructose 1,6-diphosphate, as an important sugar metabolism intermediate, can improve the energy metabolism efficiency of cells; vitamin B12 participates in DNA synthesis and cell metabolism, which helps maintain the normal function of cells. The synergistic effect of each component significantly improves the antioxidant stability, sustained release performance and environmental adaptability of the drug, providing innovative technical support for efficient drug delivery.

[0015] The present invention also provides a preparation method of a composition based on 2-oxoglutaric acid, which specifically comprises the following steps: according to parts by weight, weighing copolymer acid to encapsulate 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin, adding them into deionized water, stirring at a speed of 400-600 rpm for 30-60 min at 20-30° C.; then adding pH buffer solution, and continuing stirring for 10-20 min; then adding a bioremediation promoter and an osmotic pressure regulator, and stirring evenly at a speed of 500-800 rpm for 30-60 min at 25-35° C.; then centrifuging the mixed solution at 3000-5000 rpm for 15-30 min, taking the supernatant, and filtering through a 0.22 μm filter membrane to obtain a filtrate as the composition based on 2-oxoglutaric acid.

[0016] (3) Beneficial technical effects The present invention solves the problems of poor drug stability, uneven release and insufficient biocompatibility in the prior art through the innovative design of copolymer acid encapsulating 2-oxoglutaric acid, and significantly improves the overall performance of the drug delivery system. The molecular weight and component ratio of polylactic acid-glycolic acid copolymer acid are optimized, so that it has a suitable degradation rate and mechanical properties, gradually degrades in the body and achieves precise sustained release, effectively protecting 2-oxoglutaric acid from oxidative degradation. The average particle size of the nanoparticles prepared by the double emulsion-solvent evaporation method is controlled within the range of 100~500 nm, further enhancing the dispersibility and absorption efficiency of the drug, and at the same time, the stability and activity of the drug in a complex physiological environment are ensured by regulating the pH value of 6.8~7.2 and the osmotic pressure of 280~320 mOsm / L. As biorepair promoters, hyaluronic acid or chitosan not only promotes collagen production, but also provides tissue repair and antibacterial protection functions; mannitol or sodium chloride as osmotic pressure regulators ensures a smooth release process, and the synergistic effect of each component significantly improves the system's antioxidant, sustained-release performance and biocompatibility. Pyrroloquinoline quinone disodium salt, as an active ingredient with antioxidant and cell protection functions, can effectively reduce the damage of oxidative stress to cells; catechins further enhance free radical scavenging ability through their strong antioxidant properties, and also have the effect of protecting cardiovascular health; L-carnitine is mainly involved in fat metabolism, promotes energy generation and improves cell activity; 1,6-diphosphate fructose trisodium salt, as an important sugar metabolism intermediate, can improve the energy metabolism efficiency of cells; vitamin B12 participates in DNA synthesis and cell metabolism, which helps maintain the normal function of cells. The present invention significantly improves tissue repair ability by effectively promoting collagen production, and shows broad application prospects in the fields of beauty and skin care, anti-aging and chronic disease treatment, providing important support for industry technology upgrades. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the infrared Fourier spectrum of the polylactic acid-glycolic acid copolymer prepared in Example 1; Figure 2 This is a morphology of the copolymer acid prepared in Example 1 encapsulating 2-oxoglutaric acid; Figure 3 The results of the MTT experiment of stimulating 3T3 cells with the 2-oxoglutaric acid-based composition in Example 1 are shown.

[0018] Figure 4 The results of the MTT experiment of stimulating HaCaT cells with the 2-oxoglutaric acid-based composition in Example 1 are shown.

[0019] Figure 5 These are WB development images and grayscale analysis results of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the amount of type I collagen produced in 3T3 cells.

[0020] Figure 6 These are WB development images and grayscale analysis results of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the amount of type III collagen produced in 3T3 cells.

[0021] Figure 7 These are WB development images and grayscale analysis results of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the amount of type I collagen produced in HaCaT cells.

[0022] Figure 8 These are WB development images and grayscale analysis results of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the production of type XVII collagen in HaCaT cells.

[0023] Fig. 9 These are WB development images of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the amount of type XVII collagen produced in 3T3 cells.

[0024] Fig.10 These are WB development images of the effect of the 2-oxoglutaric acid-based composition in Example 2 on the amount of type III collagen produced in HaCaT cells.

[0025] Fig.11 The results of the MTT experiment of constructing a senescent cell model using D-galactose in Example 3.

[0026] Fig.12 This is the β-galactosidase staining result of the senescent cell model constructed using D-galactose in Example 3.

[0027] Fig.13 These are the WB development images and grayscale analysis results of the effect of D-galactose on the production of TERT protein in 3T3 cells in Example 3.

[0028] Fig.14 The results of the MTT experiment of the composition based on 2-oxoglutaric acid in Example 4 on senescent cells are shown.

[0029] Fig.15 These are the β-galactosidase staining results of the control group, senescent cell group, and senescent cell+AKG group in Example 4.

[0030] Fig.16 These are WB development images and grayscale analysis results of the effect of the 2-oxoglutaric acid-based composition on the amount of TERT protein produced in senescent cells in Example 4. DETAILED DESCRIPTION

[0031] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Example 1

[0032] A composition based on 2-oxoglutaric acid comprises the following raw materials in parts by weight: 10 parts of copolymer acid-encapsulated 2-oxoglutaric acid, 0.1 parts of nicotinamide, 0.2 parts of gamma-aminobutyric acid, 0.1 parts of superoxide dismutase, 2 parts of polyethylene glycol 400, 2.5 parts of pH buffer, 3.5 parts of bioremediation promoter, 0.5 parts of osmotic pressure regulator, 2.0 parts of beta-cyclodextrin, 50 parts of deionized water, 0.02 parts of pyrroloquinoline quinone disodium salt, 0.2 parts of catechins, 0.5 parts of L-carnitine, 0.5 parts of trisodium salt of fructose 1,6-diphosphate, and 0.002 parts of vitamin B12; the copolymer acid-encapsulated 2-oxoglutaric acid is prepared by double emulsion-solvent evaporation method, and the polylactic acid-glycolic acid copolymer acid is obtained by polymerization reaction of glycolic acid and lactic acid; The preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid of the present embodiment is as follows: in parts by weight, first, 0.5 parts of Tween 80 are dissolved in 20 parts of 2wt% citric acid aqueous solution, and then 1.25 parts of the vitamin composition are added thereto, and then 45-65 parts of 2.0wt% polyvinyl alcohol aqueous solution are added, and after mixing evenly, a solution A is obtained, and then another 2.5 parts of 2-oxoglutaric acid are evenly dissolved in 60 parts of glycerol to obtain a solution B; then 10 parts of polylactic acid-glycolic acid copolymer acid are evenly dissolved in 100 parts of ethyl acetate to obtain an organic solution; after mixing solution A and solution B evenly in a mass ratio of 1:3, the mixture is added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added to a vortex instrument container to emulsify the primary emulsion, the vortex time is 30s, the vortex instrument speed is 2000rpm, and then an ultrasonic processor is used for ultrasonication. Ultrasonic treatment, the ultrasonic conditions are 10 seconds on / off cycle each time, the ultrasonic amplitude is 60%, the frequency is 20kHz, and the number of ultrasonic treatment cycles is set to 3 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution are added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment are continued to form a double emulsion. The vortexing time is 5 minutes, and the number of ultrasonic treatment cycles is 2 times. The treated double emulsion is added to a magnetic stirrer, and the stirring rate is set to 500rpm, the stirring temperature is 30℃, and the stirring time is 240min. After stirring, solid nanoparticles are obtained; then 10 parts of solid nanoparticles and 100 parts of deionized water are mixed evenly and centrifuged at 10000rpm for 180s, and then the upper suspension after centrifugation is taken and dried under vacuum at room temperature. The vacuum condition is 40Pa and the drying time is 6h. After drying is complete, copolymer acid encapsulated 2-oxoglutaric acid is obtained.

[0033] The vitamin composition of this embodiment is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of 2.0:1:1.

[0034] The preparation method of the polylactic acid-glycolic acid copolymer acid of the present embodiment is as follows: by weight, 3.0 parts of glycolic acid, 12.9 parts of lactic acid and 3.0 parts of deionized water are stirred at 100° C. for 90 minutes, then cooled to 60° C., 0.10 parts of zinc lactate are added and stirred evenly, then heated to 160° C., stirred and reacted under vacuum for 14 hours, by-products are continuously removed by a Dean-Stark device during the reaction, the temperature is reduced to 80° C. after the reaction is completed, and then dried under vacuum for 12 hours to obtain a crude copolymer product, then the crude copolymer product is dissolved in 60 parts of ethanol to form a mixed solution, and then the mixed solution is added dropwise to a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:3, after the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove residual solvent and retain precipitate, then the obtained precipitate is dried under vacuum at 60° C. for 18 hours, and then freeze-dried at -20° C. for 36 hours to finally obtain a polylactic acid-glycolic acid copolymer.

[0035] The molecular weight of the polylactic acid-glycolic acid copolymer acid in this example is 15 kDa; the average diameter of the copolymer acid encapsulating 2-oxoglutaric acid is 100 nm.

[0036] The biorepair promoter of this embodiment is hyaluronic acid; the osmotic pressure regulator is mannitol; the pH buffer is citrate buffer, and the pH value of the composition with 2-oxoglutaric acid is 6.8, and the osmotic pressure is 280mOsm / L.

[0037] The preparation method of the composition based on 2-oxoglutaric acid of this embodiment specifically includes the following steps: according to the weight ratio, the copolymer acid encapsulated 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin are weighed and added into deionized water, and stirred at 400 rpm for 30 min at 20° C.; then the pH buffer solution is added and the stirring is continued for 10 min; then the bioremediation promoter and the osmotic pressure regulator are added and stirred evenly at 500 rpm for 30 min at 25° C.; then the mixed solution is centrifuged at 3000 rpm for 15 min, the supernatant is taken, and the filtrate obtained by filtering through a 0.22 μm filter membrane is the composition based on 2-oxoglutaric acid.

[0038] Figure 1 The infrared Fourier spectrum of the polylactic acid-co-glycolic acid copolymer prepared in Example 1 is shown, wherein at 2949, 2887, 2824 cm -1The absorption bands of CH bond stretching vibration were observed at 1622 and 1408 cm -1 Records attributed to COO - The absorption peaks of bidentate asymmetric and symmetric modes are 1747cm -1 The absorption peak of is one of the most important bands in the spectrum, belonging to the ester carbonyl group (νC=O stretching vibration) in the copolyester. -1 Two strong absorption bands belonging to the COC ester group were recorded at 2997 and 2949 cm -1 The absorption bands of υCH3 and υCH2 of lactic acid and glycolic acid units were recorded at 1452 and 1383 cm-1, respectively. In addition, the asymmetric and symmetric deformation vibrations δasCH3 and δsCH3 appeared at 1452 and 1383 cm-1, respectively. -1 , while the stretching vibration δCH is at 1267cm -1 was recorded. Figure 2 This is a morphology picture of the copolymer acid prepared in Example 1 encapsulating 2-oxoglutaric acid, and nanoparticles with uniform average particle size can be seen.

[0039] In order to evaluate the effect of the composition based on 2-oxoglutaric acid on cell viability, the MTT experiment was performed on the composition based on 2-oxoglutaric acid in this example. The specific experimental methods and results are as follows: First, BALB / 3T3 cells (mouse embryonic fibroblasts) and HaCaT cells (human epithelial keratinocytes) were selected for the experiment, respectively, and cultured at 37°C and 5% CO2. The cell density and state were observed daily under an inverted microscope. When the cells grew to 80-90% of the culture flask, the cells were passaged or inoculated. Subsequently, the cells were cultured at 3×10 3The cells were seeded at a density of 100 μM / well in a 96-well plate, four replicate wells were set up, and cultured at 37°C and 5% CO2 for 24 hours, after which they were replaced with maintenance medium for starvation treatment for 24 hours to eliminate the effects of growth factors in the culture medium on the experimental results. Next, the maintenance medium after starvation treatment was discarded, and maintenance medium containing different concentrations of 2-oxoglutaric acid-based compositions was added, with final concentrations of 0.01, 0.1, 1, 5, 10, 20, 50, 100, 200, 500, and 1000 μM, respectively. The blank control group only added maintenance medium without 2-oxoglutaric acid. Subsequently, the cells were cultured for 48 hours at 37°C and 5% CO2. In order to detect cell viability, 10 μL of MTT solution was added to each well after 48 hours of culture, and culture was continued under the same conditions for 4 hours. Then, carefully discard the supernatant in the wells (including maintenance medium and MTT solution), add 100 μL DMSO to each well, mix thoroughly, and use a microplate reader to detect the absorbance value (OD value) at a wavelength of 570 nm to reflect the cell proliferation activity. The experimental results show that (such as Figure 3-4 As shown in the results, the 2-oxoglutaric acid-based composition had no significant effect on the viability of fibroblasts (BALB / 3T3) and skin epithelial cells (HaCaT) at low to medium concentrations (≤500 μM), and only decreased cell viability at high concentrations (500 μM and 1000 μM). This shows that the 2-oxoglutaric acid-based composition has good biosafety for cells and skin tissues at conventional dosages (less than 500 μM), especially in Example 1, which shows its safety and stability. Therefore, the composition is suitable for use as an active ingredient in tissue repair products or skin care products. Example 2

[0040] A composition based on 2-oxoglutaric acid comprises the following raw materials in parts by weight: 13 parts of copolymer acid-encapsulated 2-oxoglutaric acid, 0.5 parts of nicotinamide, 0.4 parts of gamma-aminobutyric acid, 0.2 parts of superoxide dismutase, 3 parts of polyethylene glycol 400, 3.1 parts of pH buffer, 4.9 parts of bioremediation promoter, 1.7 parts of osmotic pressure regulator, 3.2 parts of beta-cyclodextrin, 56 parts of deionized water, 0.04 parts of pyrroloquinoline quinone disodium salt, 0.4 parts of catechins, 0.8 parts of L-carnitine, 1.1 parts of trisodium salt of fructose 1,6-diphosphate, and 0.008 parts of vitamin B12; the copolymer acid-encapsulated 2-oxoglutaric acid is prepared by a double emulsion-solvent evaporation method for preparing a polylactic acid-glycolic acid copolymer acid-encapsulated 2-oxoglutaric acid and vitamin composition; the polylactic acid-glycolic acid copolymer acid is obtained by polymerization of glycolic acid and lactic acid; The preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid of the present embodiment is as follows: by weight, first, 0.8 parts of Tween 80 are dissolved in 25 parts of 2wt% citric acid aqueous solution, and then 2 parts of the vitamin composition are added thereto, and then 50 parts of 2.0wt% polyvinyl alcohol aqueous solution are added, and after mixing evenly, a solution A is obtained, and then another 3.0 parts of 2-oxoglutaric acid are evenly dissolved in 68 parts of glycerol to obtain a solution B; then 13 parts of polylactic acid-glycolic acid copolymer acid are evenly dissolved in 130 parts of ethyl acetate to obtain an organic solution; after mixing solution A and solution B evenly in a mass ratio of 1:3, they are added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added to a vortex instrument container to emulsify the primary emulsion, the vortex time is 39s, the vortex instrument speed is 2300rpm, and then an ultrasonic processor is used for Ultrasonic treatment, the ultrasonic conditions are 10 seconds on / off cycle each time, the ultrasonic amplitude is 63%, the frequency is 21kHz, and the number of ultrasonic treatment cycles is set to 4 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution are added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment are continued to form a double emulsion. The vortexing time is 7 minutes, and the number of ultrasonic treatment cycles is 3 times. The treated double emulsion is added to a magnetic stirrer, and the stirring rate is set to 650rpm, the stirring temperature is 33°C, and the stirring time is 264min. After stirring, solid nanoparticles are obtained; then 12 parts of solid nanoparticles and 100 parts of deionized water are mixed evenly and centrifuged at 11500rpm for 234s, and then the upper suspension after centrifugation is taken and dried under vacuum at room temperature. The vacuum condition is 58Pa and the drying time is 8h. After drying is complete, copolymer acid encapsulated 2-oxoglutaric acid is obtained.

[0041] The vitamin composition is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of 3:1:1.

[0042] The preparation method of the polylactic acid-glycolic acid copolymer acid of the present embodiment is as follows: by weight, 3.9 parts of glycolic acid, 16.8 parts of lactic acid and 3.8 parts of deionized water are stirred at 106° C. for 105 min, then cooled to 63° C., 0.15 parts of zinc lactate are added and stirred evenly, then heated to 163° C., stirred and reacted under vacuum for 15 hours, by-products are continuously removed by a Dean-Stark device during the reaction, the temperature is reduced to 83° C. after the reaction is completed, and then dried under vacuum for 14 hours to obtain a crude copolymer product, then the crude copolymer product is dissolved in 66 parts of ethanol to form a mixed solution, and then the mixed solution is added dropwise to a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:3, after the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove the residual solvent and retain the precipitate, then the obtained precipitate is dried under vacuum at 63° C. for 20 hours, and then freeze-dried at -20° C. for 40 hours to finally obtain a polylactic acid-glycolic acid copolymer.

[0043] The molecular weight of the polylactic acid-glycolic acid copolymer acid of this embodiment is 17 kDa; the average diameter of the copolymer acid encapsulating 2-oxoglutaric acid is 220 nm.

[0044] The bioremediation promoter of this embodiment is hyaluronic acid or chitosan; the osmotic pressure regulator is mannitol or sodium chloride; the pH buffer is a mixture of phosphate buffer and citrate buffer in a mass ratio of 1:1, and the pH value of the composition based on 2-oxoglutaric acid is 6.9 and the osmotic pressure is 292mOsm / L.

[0045] The preparation method of the composition based on 2-oxoglutaric acid in this embodiment specifically includes the following steps: weighing the copolymer acid-encapsulated 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin according to weight parts, adding them to deionized water, and stirring at 460 rpm for 39 minutes at 23°C; then adding the pH buffer solution, and continuing to stir for 13 minutes; then adding the bioremediation promoter and the osmotic pressure regulator, and stirring evenly at 590 rpm for 39 minutes at 28°C; then centrifuging the mixed solution at 3600 rpm for 20 minutes, taking the supernatant, and filtering through a 0.22 μm filter membrane to obtain the filtrate as the composition based on 2-oxoglutaric acid.

[0046] In order to explore the effect of the 2-oxoglutaric acid-based composition on collagen production in different cells, WB experiments were conducted, and BALB / 3T3 cells (mouse embryonic fibroblasts) and HaCaT cells (human epithelial keratinocytes) were selected as research objects. In the experiment, the cells were cultured in a cell culture incubator at 37°C and 5% CO2. When the cell density reached 80%-90%, the cells were passaged or inoculated, and then the cells were cultured at 3×10 5The cells were inoculated at a density of 100 / well in a 6-well plate and cultured for 24 hours. After discarding the culture medium, maintenance medium containing different concentrations (0.01, 0.1, 1, 10, 50, 100, 200 μM) of the composition based on 2-oxoglutaric acid was added. The blank control group only added the maintenance medium. After continuing to culture for 48 hours, the total cell protein was extracted and the protein concentration was detected by the BCA method. Subsequently, a WB experiment was performed, and the membrane was transferred after electrophoresis. The membrane was blocked with 5% skim milk and incubated with rabbit polyclonal primary antibodies (1:1000 dilution) and HRP-labeled goat anti-rabbit IgG secondary antibodies (1:1000 dilution) against type I, type III and type XVII collagen. The information of the primary and secondary antibodies used in this example is shown in Table 1 below; the internal reference protein is β-actin (42 kDa), and grayscale analysis was performed using Image J software after development. The experimental results show that the composition based on 2-oxoglutaric acid can significantly promote the production of various collagens in different cells. The specific results are as follows: Figure 4 As described above, in 3T3 cells, the 2-oxoglutaric acid-based composition at a concentration of 1 μM and above significantly increased the production of type I collagen (COL1A1), and reached the highest level at concentrations of 10 μM and 50 μM, and then slightly decreased as the concentration further increased but still significantly higher than the control group; Figure 5 The WB image and grayscale analysis results of the effect of AKG on the amount of type I collagen produced in HaCaT cells in Example 2. Figure 6 As described, in 3T3 cells, the 2-oxoglutaric acid-based composition at a concentration of 1 μM and above significantly increased the production of type III collagen (COL3A1), and the trend was consistent with type I collagen, showing a dose-dependency; Figure 7 As described, in HaCaT cells, the 2-oxoglutaric acid-based composition at a concentration of 1 μM and above significantly promoted the production of type I collagen, reaching a peak at a concentration of 10 μM, and then slightly decreased at high concentrations; Figure 7 As described above, in HaCaT cells, the composition based on 2-oxoglutaric acid can significantly promote the production of type XVII collagen (Collagen XVII), wherein the production amount is the highest at 10 μM and 50 μM, further illustrating its promoting effect on specific collagen in epithelial cells; Fig. 9 As described above, the expression of type XVII collagen was not detected in 3T3 cells, which is consistent with the feature that type XVII collagen is mainly expressed in epithelial cells; Fig.10As described above, the expression of type III collagen was not detected in HaCaT cells, which is consistent with the characteristic that type III collagen is mainly expressed in connective tissue. Based on the above results, the composition based on 2-oxoglutaric acid can significantly promote the production of type I and type III collagen in fibroblasts, and significantly promote the production of type I and type XVII collagen in epithelial cells, showing a significant potential for promoting collagen production, verifying its role in regulating collagen synthesis in the extracellular matrix, and providing an important theoretical basis for its application in the fields of anti-aging and tissue repair.

[0047] Table 1 Information parameters of primary and secondary antibodies Example 3

[0048] A composition based on 2-oxoglutaric acid comprises the following raw materials in parts by weight: 16 parts of copolymer acid-encapsulated 2-oxoglutaric acid, 1 part of nicotinamide, 0.8 parts of gamma-aminobutyric acid, 0.4 parts of superoxide dismutase, 4.4 parts of polyethylene glycol 400, 3.7 parts of pH buffer, 6.2 parts of bioremediation promoter, 2.9 parts of osmotic pressure regulator, 4.4 parts of beta-cyclodextrin, 62 parts of deionized water, 0.06 parts of pyrroloquinoline quinone disodium salt, 0.5 parts of catechins, 1.2 parts of L-carnitine, 1.5 parts of trisodium 1,6-diphosphate fructose, and 0.012 parts of vitamin B12; the copolymer acid-encapsulated 2-oxoglutaric acid is prepared by double emulsion-solvent evaporation method for polylactic acid-glycolic acid copolymer acid-encapsulated 2-oxoglutaric acid and vitamin composition; the polylactic acid-glycolic acid copolymer acid is obtained by polymerization reaction of glycolic acid and lactic acid; The preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid of the present embodiment is as follows: by weight, first, 1.2 parts of Tween 80 are dissolved in 30 parts of 2wt% citric acid aqueous solution, and then 3.5 parts of the vitamin composition are added thereto, and then 45-65 parts of 2.0wt% polyvinyl alcohol aqueous solution are added, and after mixing evenly, a solution A is obtained, and then another 4.3 parts of 2-oxoglutaric acid are evenly dissolved in 75 parts of glycerol to obtain a solution B; then 16 parts of polylactic acid-glycolic acid copolymer acid are evenly dissolved in 160 parts of ethyl acetate to obtain an organic solution; after mixing solution A and solution B evenly in a mass ratio of 1:3, the mixture is added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added to a vortex instrument container to emulsify the primary emulsion, the vortex time is 48s, the vortex instrument speed is 2600 rpm, and then an ultrasonic processor is used for ultrasonic treatment, and the ultrasonic conditions are an on / off cycle of 10 seconds each time, an ultrasonic amplitude of 66%, and a frequency of 22.4 kHz, the number of ultrasonic treatment cycles was set to 4 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution were added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment were continued to form a double emulsion. The vortexing time was 8 minutes, and the number of ultrasonic treatment cycles was 3 times. The treated double emulsion was added to a magnetic stirrer, and the stirring rate was set to 800 rpm, the stirring temperature was 36°C, and the stirring time was 288 minutes. After stirring, solid nanoparticles were obtained; then 15 parts of the solid nanoparticles and 100 parts of deionized water were mixed evenly and centrifuged at 13000 rpm for 288 seconds, and then the upper suspension after centrifugation was taken and dried under vacuum at room temperature. The vacuum condition was 76 Pa and the drying time was 9.6 hours. After drying was complete, the copolymer acid encapsulated 2-oxoglutaric acid was obtained.

[0049] The vitamin composition of this embodiment is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of 4:1:1.

[0050] The preparation method of the polylactic acid-glycolic acid copolymer acid of the present embodiment is as follows: by weight, 4.8 parts of glycolic acid, 20.6 parts of lactic acid and 4.5 parts of deionized water are stirred at 112° C. for 120 min, then cooled to 66° C., 0.19 parts of zinc lactate are added, stirred evenly, and then heated to 166° C., stirred and reacted under vacuum for 16.4 hours, by-products are continuously removed by a Dean-Stark device during the reaction, the temperature is reduced to 86° C. after the reaction is completed, and then dried under vacuum for 17 hours. A crude copolymer product is obtained, and then the crude copolymer product is dissolved in 72 parts of ethanol to form a mixed solution, and then the mixed solution is added drop by drop into a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:3. After the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove the residual solvent and retain the precipitate, and then the obtained precipitate is dried under vacuum conditions at 66°C for 21.6h, and then freeze-dried at -20°C for 43.2h to finally obtain a polylactic acid-hydroxyacetic acid copolymer.

[0051] The molecular weight of the polylactic acid-glycolic acid copolymer acid of this embodiment is 18 kDa; the average diameter of the copolymer acid encapsulating 2-oxoglutaric acid is 340 nm.

[0052] The bioremediation promoter of this embodiment is hyaluronic acid or chitosan; the osmotic pressure regulator is mannitol or sodium chloride; the pH buffer is a mixture of phosphate buffer and citrate buffer in a mass ratio of 3:1, and the pH value of the composition based on 2-oxoglutaric acid is 7.0 and the osmotic pressure is 304 mOsm / L.

[0053] The preparation method of the composition based on 2-oxoglutaric acid in this embodiment specifically includes the following steps: weighing the copolymer acid-encapsulated 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin according to weight parts, adding them to deionized water, and stirring at 520 rpm for 48 minutes at 26°C; then adding pH buffer solution, and continuing to stir for 16 minutes; then adding a bioremediation promoter and an osmotic pressure regulator, and stirring evenly at 680 rpm for 48 minutes at 31°C; then centrifuging the mixed solution at 4200 rpm for 24 minutes, taking the supernatant, and filtering through a 0.22 μm filter membrane to obtain a filtrate as a composition based on 2-oxoglutaric acid.

[0054] D-galactose is a classic agent used to induce cells to produce a large number of free radicals and cause subacute aging. It can lead to a weakened antioxidant capacity and increased lipid levels. It is widely used to study the construction of aging models. In this example, D-galactose was used to construct an aging model of BALB / 3T3 cells (mouse embryonic fibroblasts). First, the cells were cultured at 37°C and 5% CO2. The density and state of the cells were observed daily. When the cells grew to 80-90% of the culture flask, they were passaged or inoculated. Subsequently, the cell viability was detected by MTT assay. 3×10 3 Cells were seeded in 96-well plates at a final concentration of 10, 20, and 30 mg / mL of D-galactose after 24 hours of culture. A control group was added with only maintenance medium. After 24 hours of culture, cell viability was tested according to standard methods. Then, β-galactosidase staining was used to further verify the cell senescence state. 5 Cells were seeded in 6-well plates at 1000 × 10 cells / well. After culturing for 24 hours with the same concentration of D-galactose, the cells were stained with a cell senescence β-galactosidase staining kit and the staining results were observed under an ordinary optical microscope. In addition, WB experiments were performed to detect changes in the protein expression of telomerase reverse transcriptase (TERT) and internal reference actin (β-actin). 5 Cells were seeded in 6-well plates, and D-galactose was added for stimulation for 24 hours before protein extraction. Rabbit polyclonal antibody (TERT) and HRP-goat anti-rabbit IgG secondary antibody were used for detection. Table 2 shows the information of primary and secondary antibodies used in Example 3. The experimental results show that Fig.11 As shown, D-galactose stimulation for 24 hours significantly reduced cell viability, which is consistent with the characteristics of senescent cells, and a D-galactose-induced cell senescence model was successfully constructed.

[0055] Table 2 Information on primary and secondary antibodies used in Example 3

[0056] One of the classic signs of senescent cells is the expression of β-galactosidase, whose activity can be detected by β-galactosidase staining experiment. During the detection process, the substrate X-Gal in the kit is hydrolyzed under the catalysis of β-galactosidase to generate an insoluble dark blue product. Therefore, cells that show blue staining are β-galactosidase-positive cells and are usually regarded as senescent cells. The experimental results show that if Fig.12As shown in the figure, with the gradual increase of D-galactose concentration, the number of blue-stained cells increased significantly, indicating that D-galactose can effectively induce cells to enter a state of aging. Another classic sign of aging cells is the decrease in the expression level of telomerase reverse transcriptase (TERT). As the catalytic subunit of telomerase, the expression level of TERT directly determines the activity of telomerase. Reduced TERT expression will lead to a lack of telomerase activity, and thus the inability to maintain telomere length. As cells divide, telomeres gradually shorten. When telomeres shorten to a certain extent, cells enter the aging stage. Fig.13 As shown, with the increase of D-galactose concentration, the expression level of TERT protein gradually decreased, further verifying the mechanism of D-galactose-induced cell senescence. Example 4

[0057] A composition based on 2-oxoglutaric acid comprises the following raw materials in parts by weight: 20 parts of copolymer acid-encapsulated 2-oxoglutaric acid, 1.5 parts of nicotinamide, 1.0 parts of gamma-aminobutyric acid, 0.5 parts of superoxide dismutase, 6 parts of polyethylene glycol 400, 4.5 parts of pH buffer, 8.0 parts of bioremediation promoter, 4.5 parts of osmotic pressure regulator, 6.0 parts of beta-cyclodextrin, 70 parts of deionized water, 0.1 parts of pyrroloquinoline quinone disodium salt, 0.8 parts of catechins, 2.0 parts of L-carnitine, 2.5 parts of trisodium 1,6-diphosphate fructose, and 0.02 parts of vitamin B12; the copolymer acid-encapsulated 2-oxoglutaric acid is prepared by double emulsion-solvent evaporation method for polylactic acid-glycolic acid copolymer acid-encapsulated 2-oxoglutaric acid and vitamin composition; the polylactic acid-glycolic acid copolymer acid is obtained by polymerization reaction of glycolic acid and lactic acid; The preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid of the present embodiment is as follows: in parts by weight, first, 1.5 parts of Tween 80 are dissolved in 40 parts of 2wt% citric acid aqueous solution, and then 4.5 parts of the vitamin composition are added thereto, and then 45-65 parts of 2.0wt% polyvinyl alcohol aqueous solution are added, and after mixing evenly, a solution A is obtained, and then another 4.5 parts of 2-oxoglutaric acid are evenly dissolved in 85 parts of glycerol to obtain a solution B; then 20 parts of polylactic acid-glycolic acid copolymer acid are evenly dissolved in 200 parts of ethyl acetate to obtain an organic solution; after mixing solution A and solution B evenly in a mass ratio of 1:3, they are added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added to a vortex instrument container to emulsify the primary emulsion, the vortex time is 60s, the vortex instrument speed is 3000 rpm, and then an ultrasonic processor is used for ultrasonic treatment, and the ultrasonic conditions are an on / off cycle of 10 seconds each time, an ultrasonic amplitude of 70%, and a frequency of 24 kHz, the number of ultrasonic treatment cycles was set to 5 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution were added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment were continued to form a double emulsion. The vortexing time was 10 min, and the number of ultrasonic treatment cycles was 4 times. The treated double emulsion was added to a magnetic stirrer, and the stirring rate was set to 1000 rpm, the stirring temperature was 40 °C, and the stirring time was 320 min. After stirring, solid nanoparticles were obtained; then 18 parts of solid nanoparticles and 100 parts of deionized water were mixed evenly and centrifuged at 15000 rpm for 360 s. Then, the upper suspension after centrifugation was dried under vacuum at room temperature. The vacuum condition was 100 Pa and the drying time was 12 h. After drying was complete, copolymer acid encapsulated 2-oxoglutaric acid was obtained.

[0058] The vitamin composition is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of 4.5:1:1.

[0059] The preparation method of the polylactic acid-glycolic acid copolymer acid of the present embodiment is as follows: by weight, 6.0 parts of glycolic acid, 25.8 parts of lactic acid and 5.5 parts of deionized water are stirred at 120° C. for 140 minutes, then cooled to 70° C., 0.25 parts of zinc lactate are added, stirred evenly, and then heated to 170° C., stirred and reacted for 18 hours under vacuum, by-products are continuously removed by a Dean-Stark device during the reaction, the temperature is reduced to 90° C. after the reaction is completed, and then dried under vacuum for 20 hours to obtain a crude copolymer product, then the crude copolymer product is dissolved in 80 parts of ethanol to form a mixed solution, and then the mixed solution is added dropwise to a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:3, after the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove the residual solvent and retain the precipitate, then the obtained precipitate is dried under vacuum at 70° C. for 24 hours, and then freeze-dried at -20° C. for 48 hours, to finally obtain a polylactic acid-glycolic acid copolymer.

[0060] The molecular weight of the polylactic acid-glycolic acid copolymer acid in this example is 20 kDa; the average diameter of the copolymer acid encapsulating 2-oxoglutaric acid is 500 nm.

[0061] The biorepair promoter of this embodiment is hyaluronic acid; the osmotic pressure regulator is mannitol; the pH buffer is phosphate buffer, and the pH value of the composition based on 2-oxoglutaric acid is 7.2, and the osmotic pressure is 320 mOsm / L.

[0062] The preparation method of the composition based on 2-oxoglutaric acid of this embodiment specifically includes the following steps: weighing the copolymer acid encapsulated 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin according to weight parts, adding them to deionized water, and stirring at 600 rpm for 60 minutes at 30°C; then adding pH buffer solution, and continuing stirring for 20 minutes; then adding a bioremediation promoter and an osmotic pressure regulator, and stirring evenly at 800 rpm for 60 minutes at 35°C; then centrifuging the mixed solution at 5000 rpm for 30 minutes, taking the supernatant, and filtering through a 0.22 μm filter membrane to obtain a filtrate as a composition based on 2-oxoglutaric acid.

[0063] The anti-aging activity of α-ketoglutarate (AKG) was experimentally verified using the D-galactose-induced cell senescence model constructed in Example 3. First, BALB / 3T3 cells were cultured to 80-90% confluence and then passaged. They were seeded in 96-well plates or 6-well plates according to the method in Example 3 and treated with 30 mg / mL of D-galactose for 24 hours to construct a senescent cell model. Only maintenance medium was added to the control group. Subsequently, the culture medium was discarded, and different concentrations (1, 2, 3, and 4 mM) of AKG were added for stimulation. Only maintenance medium was added to the control group. After continuing to culture for 24 hours, MTT experiments, β-galactosidase staining experiments, and WB experiments were performed to detect relevant indicators. The experimental results showed that Fig.14 As shown in the figure, D-galactose treatment caused a significant decrease in cell viability, while AKG could significantly improve the viability of senescent cells, and the effect was optimal at a concentration of 2 mM. After exceeding this concentration, the viability improvement was no longer significant. Therefore, 2 mM AKG was used for subsequent staining experiments and WB experiments. β-galactosidase staining results ( Fig.15 ) showed that the number of blue-stained cells increased significantly after D-galactose treatment, while the number of blue-stained cells decreased significantly after 2 mM AKG stimulation, with no significant difference compared with the control group, indicating that AKG can effectively reduce the number of senescent cells. WB experimental results ( Fig.16 ) further verified the anti-aging effect of AKG. D-galactose treatment led to a significant decrease in TERT protein levels, while 2 mM AKG stimulation significantly restored TERT protein levels. In summary, AKG showed significant anti-aging activity by improving cell viability, reducing the number of senescent cells, and restoring TERT protein levels.

[0064] Comparative Example 1 The method is basically the same as Example 1, except that 2-oxoglutaric acid is not coated, but 2-oxoglutaric acid, polylactic acid-co-glycolic acid acid and the vitamin composition are added separately.

[0065] In this comparative example, compared with Example 1, 2-oxoglutaric acid was not coated, but was added to the composition in the form of separate additions with polylactic acid-co-glycolic acid copolymer acid and vitamin composition. Due to the lack of coating protection, the stability of 2-oxoglutaric acid in solution is significantly reduced, and it is prone to oxidation or degradation, resulting in a decrease in its biological effectiveness. At the same time, the uncoated form cannot achieve a sustained release effect, the peak efficacy rapidly decays, and it is difficult to continue to exert its effect. In addition, the synergistic protection and stability advantages provided by the coating technology are weakened, and the overall effect is reduced. The experimental results show that compared with Example 1, the amount of collagen produced in this comparative example is significantly reduced, and the effect is unstable.

[0066] Comparative Example 2 The method is basically the same as Example 1, except that chitosan is not added to the copolymer acid-encapsulated 2-oxoglutaric acid.

[0067] This comparative example is basically the same as Example 1, but chitosan is not added to the 2-oxoglutaric acid nanoparticles coated with copolymer acid. The stability and functionality of the 2-oxoglutaric acid nanoparticles coated with copolymer acid are significantly reduced. Specifically, the particle size of the nanoparticles increases, the dispersibility becomes worse, and the encapsulation efficiency and drug release performance are reduced. This shows that chitosan plays an important role in the formation and stabilization of nanoparticles, and its addition can effectively improve the structure and performance of nanoparticles. Specifically, the promotion effect on collagen synthesis and secretion is significantly lower than that in Example 1. The lack of chitosan may lead to a decrease in the structural stability of the nanoparticles, thereby affecting the release efficiency of 2-oxoglutaric acid and its regulatory effect on pathways related to collagen metabolism. This shows that chitosan not only plays a key role in the stability of nanoparticles, but also has an important contribution to its biological activity, especially the effect of enhancing collagen production.

[0068] Comparative Example 3 It is basically the same as Example 1, except that no bioremediation promoter is added to the composition.

[0069] In this comparative example, compared with Example 1, no biorepair promoter (such as hyaluronic acid or chitosan) was added to the composition. Biorepair promoters play an important role in promoting extracellular matrix repair, maintaining cell activity and providing a suitable microenvironment. Their absence will significantly weaken the ability of the composition to promote collagen production and tissue repair effects. In particular, the moisturizing effect of hyaluronic acid helps to maintain cell activity, while chitosan can support the reconstruction of the extracellular matrix. The experimental results show that the amount of collagen produced in this comparative example is significantly reduced compared with Example 1, and the cell activity and tissue repair ability are also reduced.

[0070] Comparative Example 4 The method is substantially the same as Example 1, except that no osmotic pressure regulator is added to the composition.

[0071] The main difference between this comparative example and Example 1 is that no osmotic pressure regulator (such as mannitol or sodium chloride) is added to the composition. The osmotic pressure regulator is used to maintain the osmotic pressure balance of the composition so that it is close to the physiological range (280~320 mOsm / L). Without the addition of an osmotic pressure regulator, the osmotic pressure of the composition may deviate from the physiological range, causing cell expansion or contraction, destroying the normal growth environment of the cells, and thus affecting the cell's absorption efficiency of the active ingredients. The experimental results show that the amount of collagen produced in this comparative example is significantly lower than that in Example 1, and the cell activity and tissue repair function are significantly weakened.

[0072] Comparative Example 5 It is basically the same as Example 1, except that no pH buffer is added to the composition.

[0073] In this comparative example, compared with Example 1, no pH buffer (such as phosphate buffer or citrate buffer) is added to the composition. The function of the pH buffer is to maintain the pH value of the composition within the physiological range (6.8-7.2) to ensure the stability of the 2-oxoglutaric acid and vitamin composition. When the pH buffer is not added, the pH value of the composition may fluctuate, resulting in accelerated degradation of the active ingredients and affecting the acid-base balance of the cell growth environment. The experimental results show that the amount of collagen produced in this comparative example is lower than that in Example 1, especially during long-term use, the collagen-promoting effect is significantly weakened.

[0074] In summary, through the comparative analysis of each comparative example and Example 1, it can be clearly seen that the synergistic effect of the coating treatment of 2-oxoglutaric acid, chitosan, biorepair promoter, osmotic pressure regulator and pH buffer is the key to achieving the efficient and stable performance of the composition. The coating treatment significantly improves the stability and sustained release effect of 2-oxoglutaric acid, chitosan plays an important role in antioxidant protection and promoting collagen synthesis, the biorepair promoter effectively promotes extracellular matrix repair and cell activity, and the osmotic pressure regulator and pH buffer ensure the environmental adaptability and component stability of the composition. The absence of any one component will lead to a significant decrease in collagen production and tissue repair ability, which verifies the scientificity and necessity of the formula design in Example 1, and provides a solid theoretical basis and experimental support for subsequent optimization and application.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A composition based on 2-oxoglutaric acid, characterized in that The invention comprises the following raw materials in parts by weight: 10-20 parts of copolymer acid-coated 2-oxoglutaric acid, 0.1-1.5 parts of nicotinamide, 0.2-1.0 parts of gamma-aminobutyric acid, 0.1-0.5 parts of superoxide dismutase, 2-6 parts of polyethylene glycol 400, 2.5-4.5 parts of pH buffer, 3.5-8.0 parts of bioremediation promoter, 0.5-4.5 parts of osmotic pressure regulator, 2.0-6.0 parts of beta-cyclodextrin, 50-70 parts of deionized water, 0.02-0.1 parts of pyrroloquinoline quinone disodium salt, 0.2-0.8 parts of catechin, 0.5-2.0 parts of L-carnitine, 0.5-2.5 parts of trisodium fructose 1, 6-diphosphate, and 0.002-0.02 parts of vitamin B12; The copolymer acid-encapsulated 2-oxoglutaric acid is prepared by double emulsification-solvent evaporation method to prepare the polylactic acid-glycolic acid copolymer acid-encapsulated 2-oxoglutaric acid and vitamin composition; The polylactic acid-glycolic acid copolymer is obtained by polymerization of glycolic acid and lactic acid.

2. A composition based on 2-oxoglutaric acid as claimed in claim 1, characterized in that The preparation method of the copolymer acid-encapsulated 2-oxoglutaric acid is as follows: first, by weight, 0.5-1.5 parts of Tween 80 are dissolved in 20-40 parts of a 2wt% citric acid aqueous solution, then 1.25-4.5 parts of a vitamin composition are added thereto, then 45-65 parts of a 2.0wt% polyvinyl alcohol aqueous solution are added, and after uniform mixing, a solution A is obtained, and then 2.5-4.5 parts of 2-oxoglutaric acid are uniformly dissolved in 60-85 parts of glycerol to obtain a solution B; then 10-20 parts of polylactic acid-glycolic acid copolymer acid are uniformly dissolved in 100-200 parts of ethyl acetate to obtain an organic solution; after uniform mixing of the solution A and the solution B in a mass ratio of 1:3, the solution A and the solution B are added dropwise into the organic solution to form a primary emulsion, and then the primary emulsion is added into a vortex instrument container to emulsify the primary emulsion, the vortex time is 30-60s, and the speed of the vortex instrument is 2000-3000. rpm, then use an ultrasonic processor for ultrasonic treatment, the ultrasonic conditions are 10 seconds on / off cycle each time, the ultrasonic amplitude is 60~70%, the frequency is 20~24 kHz, and the number of ultrasonic treatment cycles is set to 3~5 times. After the ultrasonic treatment, 50 parts of 4wt% PVA aqueous solution are added to 100 parts of the primary emulsion after ultrasonic treatment, and vortexing and ultrasonic treatment are continued to form a double emulsion. The vortexing time is 5~10min, and the number of ultrasonic treatment cycles is 2~4 times. The treated double emulsion is added to a magnetic stirrer, and the stirring rate is set to 500~1000 rpm, the stirring temperature is 30~40℃, and the stirring time is 240~320min. After the stirring is completed, solid nanoparticles are obtained; then 10~18 parts of solid nanoparticles and 100 parts of deionized water are mixed evenly and centrifuged at 10000~15000rpm for 180~360s, and then the upper suspension after centrifugation is taken and dried under vacuum at room temperature. The vacuum conditions are 40~100 Pa, the drying time is 6 to 12 hours, and after complete drying, the copolymer acid encapsulating 2-oxoglutaric acid is obtained.

3. A composition based on 2-oxoglutaric acid as claimed in claim 2, characterized in that, The mass ratio of the vitamin composition to 2-oxoglutaric acid is (0.5-1.0):1; The vitamin composition is prepared by mixing vitamin D, vitamin B1 and vitamin B2 in a mass ratio of (2.0-4.5):1:

1.

4. A composition based on 2-oxoglutaric acid as claimed in claim 2, characterized in that The preparation method of the polylactic acid-glycolic acid copolymer acid is as follows: by weight, 3.0-6.0 parts of glycolic acid, 12.9-25.8 parts of lactic acid and 3.0-5.5 parts of deionized water are stirred at 100-120° C. for 90-140 minutes, then cooled to 60-70° C., 0.10-0.25 parts of zinc lactate are added, stirred evenly, and then heated to 160-170° C., stirred and reacted under vacuum for 14-18 hours, and the reaction was continuously carried out by a Dean-Stark device. The by-products are removed, and after the reaction is completed, the temperature is reduced to 80-90°C, and then dried under vacuum conditions for 12-20 hours to obtain a crude copolymer product, and then the crude copolymer product is dissolved in 60-80 parts of ethanol to form a mixed solution, and then the mixed solution is added dropwise to a mixed solution of 200 parts of methanol and water, wherein the volume ratio of methanol to water is 1:

3. After the dropwise addition is completed, the mixed solution is separated by decantation and centrifugation to remove the residual solvent and retain the precipitate, and then the obtained precipitate is dried under vacuum conditions at 60-70°C for 18-24 hours, and then freeze-dried at -20°C for 36-48 hours to finally obtain a polylactic acid-glycolic acid copolymer.

5. A composition based on 2-oxoglutaric acid as claimed in claim 4, characterized in that The molecular weight of the polylactic acid-glycolic acid copolymer is 15-20 kDa.

6. A composition based on 2-oxoglutaric acid as claimed in claim 1 or 2, characterized in that: Furthermore, the average diameter of the copolymer acid encapsulated 2-oxoglutaric acid is 100-500 nm.

7. A composition based on 2-oxoglutaric acid as claimed in claim 4, characterized in that The mass ratio of the glycolic acid to the lactic acid is 1:4.

3.

8. A composition based on 2-oxoglutaric acid as claimed in claim 1, characterized in that, The biorepair promoter is hyaluronic acid or chitosan; The osmotic pressure regulator is mannitol or sodium chloride; The pH buffer is a phosphate buffer or a citrate buffer or a mixture of the two.

9. A composition based on 2-oxoglutaric acid as claimed in claim 1, characterized in that, The pH value of the composition is 6.8-7.2, and the osmotic pressure is 280-320 mOsm / L.

10. A method for preparing a composition based on 2-oxoglutaric acid according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the weight proportions, the copolymer acid-encapsulated 2-oxoglutaric acid, polyethylene glycol 400 and β-cyclodextrin are weighed and added into deionized water, and stirred at a speed of 400-600 rpm for 30-60 min at 20-30° C.; then the pH buffer solution is added, and stirring is continued for 10-20 min; then the bioremediation promoter and the osmotic pressure regulator are added, and stirring is uniformly carried out at a speed of 500-800 rpm for 30-60 min at 25-35° C.; then the mixed solution is centrifuged at 3000-5000 rpm for 15-30 min, the supernatant is taken, and the filtrate obtained by filtering through a 0.22 μm filter membrane is a composition based on 2-oxoglutaric acid.

Citation Information

Patent Citations

  • An antimicrobial peptide sustained-release microsphere formulation and its preparation method

    CN102274485A

  • Preparation method of ivermectin sustained-release microspheres

    CN102302457A

  • Nutritional compositions having alpha-hica and alpha-ketoglutarate

    CN103476274A

  • Polylactic acid-cyclodextrin inclusion compound and preparing method, product and application thereof

    CN105585743A

  • Seaweed extract healthcare product having anti-aging effect and preparation method of seaweed extract healthcare product

    CN106692955A

Cited By

  • Composition for skin repair and anti-aging and preparation method thereof

    CN121059467A